2021
DOI: 10.3389/fneur.2021.678198
|View full text |Cite
|
Sign up to set email alerts
|

Central Post-Stroke Pain: An Integrative Review of Somatotopic Damage, Clinical Symptoms, and Neurophysiological Measures

Abstract: Introduction: The physiopathology of central post-stroke pain (CPSP) is poorly understood, which may contribute to the limitations of diagnostic and therapeutic advancements. Thus, the current systematic review was conducted to examine, from an integrated perspective, the cortical neurophysiological changes observed via transcranial magnetic stimulation (TMS), focusing on the structural damage, and clinical symptoms in patients with CPSP.Methods: The literature review included the databases EMBASE, PubMed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 161 publications
(210 reference statements)
0
17
0
Order By: Relevance
“…Our results support that these are genuine findings in CNP and suggest these are not uniquely related to corticospinal motor injury or non-specific effects of chronic pain in general (e.g., sleep abnormalities, mood, fatigue) or to psychotropic analgesic medication use. Among the CE measures, MEP is one of the most studied parameters in cortical clinical neurophysiology [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support that these are genuine findings in CNP and suggest these are not uniquely related to corticospinal motor injury or non-specific effects of chronic pain in general (e.g., sleep abnormalities, mood, fatigue) or to psychotropic analgesic medication use. Among the CE measures, MEP is one of the most studied parameters in cortical clinical neurophysiology [5].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the motor cortex could serve as an entry gate allowing for modulation of neuronal activity when targeted by neuromodulatory interventions but equally allowing for a read-out of part of the global excitability status of extra-motor areas by means of CE measurements. Despite the potential to probe the corticomotor system to gain mechanistic insights into the development of CNP, the available data is based on a small number of patients, either lacking a control group or using healthy individuals as comparators [5].…”
Section: Introductionmentioning
confidence: 99%
“…When pain is related to the stroke, amitriptyline, lamotrigine, and GABA receptor agonist are advised as first-line pharmacotherapeutic options [ 61 ]. Also, non-pharmacotherapeutic interventional therapies such as motor cortex stimulation or transcranial magnetic stimulation have been shown to provide relief in difficult-to-treat patients [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The infarcted site in this case is MO. Studies [ 16 , 19 ] have shown that lateral MO infarction is more likely to cause burning pain on the contralateral body, which may be caused by the stimulation to the lateral spinothalamic tract. The anatomic sequence of lateral spinothalamic tract from the lateral to the middle is sacral, lumbar, thoracic, and cervical, so patients with lateral MO infarction are prone to paresthesia of the lower limb at the onset and then upper limb paresthesia becomes obvious, [ 20 ] which is consistent with this case.…”
Section: Discussionmentioning
confidence: 99%